Análise do nível de gestão da sustentabilidade na rede hoteleira de Foz do Iguaçu, PR, utilizando como suporte a contabilidade gerencial - Ferreira, Júlio César (2017)
The emphasis on the urgency of humanity development compatible with current and future needs – named sustainable development – has had an impact on a number of sectors. The concern about sustainability extends to the tourism sector, especially to the means of lodging, which implements actions seeking to obey the principles of sustainability. Based on this argument, it was decided to investigate and to analyze the level of sustainability management of hotels in Foz do Iguaçu, PR. In order to achieve this objective, hotels associated with the Brazilian Hotel Industry Association (ABIH) were selected to compose the sample, being the main objective of this study the use of Managerial Accounting as a support, through the model proposed by Callado (2010). Thus, the following strategy was carried out: description of the importance of sustainability in hotels management; discussion and presentation of the applicability of theoretical models of sustainability indicators; measurement of the level of sustainability of the hotel companies of Foz do Iguaçu, PR, using the Grid model of Corporate Sustainability (GSE). The research was characterized, regarding the objectives, as exploratory and descriptive, since the existing situations in the studied companies was described, identified, reported and compared, and the scientific contributions that were made on the sustainable development of the hotels were investigated. Concerning the technical procedures of this research, it was classified as bibliographic and survey. Regarding the problem approach, it was characterized as qualitative, since it highlighted the perception of the subjects about the research’s theme, as well as confronted and validated the results. As a result, this research has shown that most of the hotels investigated do not have satisfactory sustainable performances in the three dimensions. Regarding the Environmental dimension, it was observed that 61% of the hotels performed satisfactorily, while 39% of the hotels had unsatisfactory results. In the economic dimension, it was observed that only 30% of hotels presented satisfactory performances. The remaining 70% of hotels performed below average in this dimension. In the social dimension, 35% of the 23 hotels presented satisfactory performances in the Partial Social Sustainability Scores. The other 65% hotels performed below average in this area. It can be asserted that this research contributed with important information on the profile of hotel management, both for the sustainable development in the environmental, economic, and social aspects, as well as for the efficiency of the environmental management of its enterprises in the search of Corporate Sustainability. Finally, the Managerial accounting, as an indispensable tool to assist strategies and decisions of hotel companies, provides timely and highly relevant information, so that the administration can make coherent and safe decisions in the scope of Corporate Sustainability.